Utility of nintedanib for severe idiopathic pulmonary fibrosis: a single-center retrospective study [Response to letter] - Abe M; Tsushima K; Tatsumi K (Dove Medical Press, 2019)
Mitsuhiro Abe,1 Kenji Tsushima,1,2 Koichiro Tatsumi11Department of Respirology, Graduate School of Medicine, Chiba University, Chuo-ku, Chiba city, Chiba 260-8670, Japan; 2Department of Pulmonary Medicine, International University of Health and Welfare, School of Medicine, Narita city, Chiba 286-8686, JapanIn our study, we observed that even in Severe Group of patients with interstitial pulmonary fibrosis (IPF), nintedanib administration suppressed the reduction in the forced vital capacity (FVC) (Figure 3).1 However, the frequency of side effects tended to be more (Table 2) and the prognosis was significantly worse in Severe Group than in Mild Group (Figure 5).View the original paper by Orsatti and colleagues.